Nanoprecipitates induced dislocation pinning and multiplication strategy for designing high strength, plasticity and conductivity Cu alloys. (1st April 2021) - Yang, Huiya; Li, Keqiang; Bu, Yeqiang; Wu, Jinming; Fang, Youtong; Meng, Liang; Liu, Jiabin; Wang, Hongtao
Abstract: A nanoprecipitates induced dislocation pinning and multiplication strategy is proposed for designing Cu alloys with high strength, plasticity and conductivity. That is, the nanoprecipitates act as obstacles and sources of dislocations. Additionally, the precipitation purifies the Cu matrix to guarantee the conductivity. To verify this strategy, dense dislocations and nanoprecipitates are introduced to a Cu-Fe-Ti alloy by solution treatment, rolling and aging. In-situ transmission electron microscopy straining and molecular dynamics simulations demonstrate that nanoprecipitates not only hinder the dislocation glide but also facilitate the dislocation multiplication, resulting in a tensile strength of 590 MPa combined with a uniform elongation of 6% of the alloy. The purification of the Cu matrix by the precipitation leads to an electrical conductivity of 69% IACS. Hence, this strategy paves a new avenue for developing high strength, high plasticity and high conductivity alloys. Graphical abstract: Image, graphical abstract